Federal Funds Rate Spillover Effect On Emerging Market Banking Liquidity And Capital – Evidence From Indonesia - Ridho, Wahyu Fahrul (Universitas Muria Kudus, 2023)
This paper examines the spillover effect of the fed fund rate (FFR) on emerging banking liquidity and capital in emerging markets, especially in Indonesia, using the Structural Equation Model (SEM). Data were collected from the Indonesia Central Bank and Financial Services Authority. Our model reveals a significant indirect negative relationship between FFR, banking liquidity, and capital. This relationship was examined both directly and indirectly using the model. While the FFR influence was robust, the impact on liquidity and capital was translated through the local bank rates. It is found that rising interest rates would still result in tighter liquidity to some extent. FFR also impacts capital decisions because the rising interest rate might incentivize managers to borrow from a lower market environment. Thus, observing the indirect relationship, the impact of the FFR depends on the local central bank monetary policy transmission to mitigate the spillover effect resulting from developed economy monetary policy.